Phase Ib trial of lenalidomide as post-remission therapy for older adults with acute myeloid leukemia: Safety and longitudinal assessment of geriatric functional domains. Issue 4 (May 2022) - Woods, Justin D.; Zeidner, Joshua F.; Van Deventer, Hendrik W.; Jamieson, Katarzyna; Matson, Melissa; Zhang, Jack; Pulley, William; Brenizer, Tucker; Muss, Hyman; Nyrop, Kirsten A.; Vohra, Sanah N.; Deal, Allison M.; et al.
Abstract: Background and Objectives: Novel, non-cytotoxic agents are driving a paradigm shift for treatment of older adults with acute myeloid leukemia (AML). Older patients who initially receive intensive cytotoxic induction may choose to not proceed with cytotoxic consolidation therapy. Lenalidomide is an orally-administered immunomodulatory small molecule with activity in AML and a favorable safety profile in older adults with active leukemia. We conducted a phase Ib study of lenalidomide as post-remission therapy in older adults and assessed its impact on geriatric functional domains. Materials and Methods: Participants were patients with AML over age 60 years who had undergone induction therapy and were poor candidates for cytotoxic consolidation. Lenalidomide was administered for 28 days in three dose cohorts. A Bayesian dose-escalation method determined cohort assignment and maximum tolerated dose (MTD). Geriatric assessment (GA) was performed before and after the cycle of lenalidomide. Results: Nineteen patients with median age 68 were treated with at least one 28-day course of lenalidomide. Dose-limiting toxicities were observed in three participants at 25 mg, zero participants at 35 mg, and one participant at 50 mg. MTD was 35 mg. Median relapse-free survival was 4.3 months. GA was completed before and after treatment in fifteen patients, demonstrating improved cognitive function and no changes in physical, psychological, or social function after lenalidomide. Conclusion: Lenalidomide can be safely administered to older adults with AML with preservation of functional domains important to older patients. Serial GA can be performed in a novel drug study as a tool to characterize treatment tolerability.